1986
DOI: 10.1136/vr.119.2.31
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of diarrhoea in young calves

Abstract: Faeces samples were collected from 302 untreated calves on the day of onset of diarrhoea and from 49 healthy calves at 32 farms experiencing outbreaks of diarrhoea. At least four diarrhoeic calves were sampled on each farm, and samples were examined for rotavirus, coronavirus, cryptosporidium, enterotoxigenic Escherichia coli and Salmonella species. Although all these enteropathogens were excreted more frequently by the diarrhoeic than by the healthy calves, the difference was significant overall only for rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
135
7
18

Year Published

1991
1991
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(189 citation statements)
references
References 0 publications
17
135
7
18
Order By: Relevance
“…The origin and the pathogenicity of these atypical ETEC is unclear. In contrast to other reports [26,27], ETEC was detected with similar frequencies in all age groups (0-45 days) and no association between infection and diarrhoea was found. Thus, it seems possible that these strains could act as a reservoir of virulence factors more than as pathogens.…”
Section: Clinical Characteristics Of the Outbreakscontrasting
confidence: 54%
“…The origin and the pathogenicity of these atypical ETEC is unclear. In contrast to other reports [26,27], ETEC was detected with similar frequencies in all age groups (0-45 days) and no association between infection and diarrhoea was found. Thus, it seems possible that these strains could act as a reservoir of virulence factors more than as pathogens.…”
Section: Clinical Characteristics Of the Outbreakscontrasting
confidence: 54%
“…Previous studies also showed no association between Cryptosporidium spp. infection and diarrhea in cattle [24,30].…”
Section: Discussionmentioning
confidence: 99%
“…It is involved in the etiology of neonatal diarrhea in calves and winter dysentery of adult cows in many countries, including Brazil (3,9,16,18). It may also be involved in infections of the respiratory tract in calves (2,20).…”
Section: Introductionmentioning
confidence: 99%